Preservation and extension of shelf life of Malus domestica using edible coating - Patekar, Shruti K; Sarma, Gopa (Journal of Postharvest Technology, 2023)
Fruits and vegetables are rich sources of micronutrients and macronutrients. They are reservoirs of antioxidants, bio-flavonoids, dietary fibres  and flavouring compounds. Consumption of fruits and vegetables reduces the development of chronic diseases such as hypertension, coronary  heart disease, asthma, etc. Apple (Malus domestica) is a commercially important fruit that is widely produced and consumed throughout the  world. Fruits have short shelf life due to their perishable nature. Storage of fruits, post harvesting is one of the serious problems as they are  prone to deterioration during handling, transport and storage. One of the major growth segments in food retail industry comprises of fresh and  minimally processed fruits and vegetables. Wax coating is used mainly to preserve the fruits and to refract its colour which can be carcinogenic.  Edible coating is one of the potential approaches for meeting this demand. The present study is carried out to increase the shelf life of apple  using edible coating of gum Arabic in various concentration (3%, 5%, and 10%) along with aqueous solution of apple peel. It is observed that  the use of a coating of gum Arabic and aqueous solution of apple peel retains the post-harvest fruit quality as compare to uncoated (control) fruit. The fruits were stored at room temperature for 14 days. Physiological loss in weight, pH, and sensory characteristics (colour, taste, and  firmness) were analyzed at regular intervals during the storage period. The coated fruits survived the storage period of 14 days, whereas all the  uncoated fruits (control) decayed within 14 days.
Keywords: Edible coating; Gum Arabic; Apple; , sensory evaluation,; shelf life.